Citizenship and Migration in the Era of Globalization The Flow of Migrants and the Perception of Citizenship in Asia and Europe - Pohlmann, Markus.; Yang, Jonghoe.; Lee, Jong-Hee. (Transcultural Research Heidelberg Studies on Asia and Europe in a Global Context, 2013)
In an age of globalizationthere is frequent migration across national borders, resulting in a reconsideration of the notion, practice and social institution of national citizenship. Addressing this phenomenon, the book focuses on the exchange between, and responses, of Korea and Germany. In particular, the book deals extensively with citizenship in Korea where the concept of citizenship is young, and thus the study of citizenship is relatively scarce. This book may be the first of its kind, bringing together eminent Korean and German scholars to analyse various aspects of citizenship in Korea. It is hoped that it will contribute to scholarship in the fields of citizenship and migration and to an understanding of the flow of people and ideas between Asia and Europe.